Case Report: Supramalleolar osteotomy to preserve joint function and delay the development of Charcot neuroarthropathy of the ankle - Zhang, Baozhou; Li, Wenjing; Li, Ying; Du, Hui; Wu, Yong (Frontiers in Surgery, 2023)
Background Charcot neuroarthropathy (CN) is a severe disease that primarily affects the foot and ankle. Conservative treatment with total contact casts is suitable for early stages, but surgery is necessary for complications such as ulceration, malalignment, infection, or severe pain. The ankle instability caused by excessive axial load may require arthrodesis. However, preserving joint function in young patient can significantly enhance the quality of life.Case report A 33-year-old woman underwent open reduction and internal fixation after the right tibia and fibula fractures following a fall while walking. She developed severe pain and deformity in her right ankle after full weightbearing. After further evaluation, she was diagnosed with Charcot neuroarthropathy (CN) of the right ankle. The patient declined arthrodesis and opted for a supramalleolar osteotomy (SMO) instead 18 months after the initial surgery. The SMO procedure involved correcting the hindfoot malalignment through osteotomy and fixation. Although she experienced skin necrosis, the patient eventually achieved satisfactory outcomes with improvements in pain, deformity, and functionality of the ankle. Radiographic measurements showed positive realignment, and the patient reported a significant improvement in her quality of life at the final follow-up.The SMO procedure could potentially be considered as an option to preserve ankle function and delay the disease development of CN for young patients.The restored foot stability and hindfoot alignment can help improve patients' quality of life.